Kesesuaian Penggunaan Bahan Tambahan Pangan pada Bumbu Olahan Skala Industri Rumah Tangga Pangan di Jawa Timur - Aida Khoirullisa; Retno Anggrina Khalistha Dewi; Sutrisno Koswara; Winiati P. Rahayu (Jurnal Mutu Pangan : Indonesian Journal of Food Quality, 2026)
The appropriate use of food additives in accordance with regulatory standards is one of the commitments that home food industry actors must fulfil after the issuance of distribution permits. Spice products are among the food items produced by home food industries and often involve the use of food additives during production. This study aimed to analyze the types and groups of food additives and to evaluate their compliance with food categories in seasoning products processed by IRTP. Secondary data were obtained from the SPP-IRT application for the East Java region specifically the composition of spices products. Home food industry’s spice products consisted of five groups, of which three groups of products met the criteria for sampling in this study, namely sauces and similar products, spices and condiments, and processed soybean spices and sauces. Analysis of 118 samples revealed the use of food additives from 12 different categories. Food additives classified under GMP maximum limit types were more prevalent, accounting for 58% of the usage within industry. The overall compliance rate for the use of food additives in seasoning products was 69%. Instances of non-compliance included the use of food additives inconsistent with the designated food category (10%) and the omission of specific food additives' names in the product composition data by producers (15%). These results highlight the necessity of education and stricter control for home food industries regarding the use of food additives in seasoning.